Design and development of Spherical Amphibian Vehicle (SAV) - Mohd Bazli, Bahar; Mohd Shahrieel, Mohd Aras; Shahrum Shah, Abdullah; San, Ng Sin; Zainah, Md Zain; Ahmad Anas, Yusof; Mohd Zaidi, Mohd Tumari (Springer Science and Business Media Deutschland GmbH, 2022)
Spherical Amphibian Vehicle (SAV) is a spherical robot that is capable of operating in two different environments which are terrestrial and underwater. SAV has a wide range of applications in scientific research and military activities such as ocean exploration and search and rescue missions. However, motion control of a spherical robot is a very challenging task because of the nonlinearity of the robot system, time-variance, uncertainty external disturbances and difficulty in hydrodynamic modelling. This project is focused on building a SAV that is cost-efficient and able to function on land and underwater. The designed robot is a 2 degree of freedom (DoF) movement that can move forward/reverse and left/right direction. It uses one DC motor and one servo motor to actuate the forward/reverse motion and sideways (left/right) motion, respectively. Arduino UNO is selected to be used as a microcontroller due to its effectiveness and low cost. The spherical amphibian robot is designed with Arduino bluecontrol interface.